Cerebroprotein hydrolysate attenuates neurodegenerative changes in Alzheimer’s mice model via ferroptosis pathway - Chen, Moxi; Song, Wei; Chen, Zhengju; Shi, Xiaodong; Wang, Xue; Li, Rongrong; Hao, Honglin; Chen, Wei (Frontiers in Pharmacology, 2023)
Introduction: Cerebroprotein hydrolysate has been proven to improve cognitive function in patients with Alzheimer’s disease (AD). We explored the safety and effectiveness of the clinical administration of oral cerebroprotein hydrolysate in AD, and possible mechanisms related to the neuronal ferroptosis pathway. Methods: Three-month-old male APP/PS1 double-transgenic mice were randomly divided into AD model (n=8) and intervention (n=8) groups. Eight non-transgenic wild-type (WT) C57 mice were used as age-matched controls. The experiments were started at the age of 6 month. The intervention group was then administered cerebroprotein hydrolysate nutrient solution (11.9 mg/kg/day) via chronic gavage, the other groups received an identical volume of distilled water. Behavioural experiments were performed after 90 days of continuous administration. Serum and hippocampal tissues were then collected for histomorphological observation, tau and p-tau expression, and ferroptosis markers analysis. Results: Cerebroprotein hydrolysate simplified movement trajectories and shortened escape latencies of APP/PS1 mice in the Morris water maze test. Neuronal morphologies were restored in hippocampal tissues on haematoxylin-eosin staining. In the AD-model group, Aβ protein and p-tau/tau expression levels were elevated, plasma Fe2+ and malondialdehyde levels were elevated, GXP4 protein expression and plasma glutathione levels declined than controls. All indices improved after cerebroprotein hydrolysate intervention. Conclusion: Cerebroprotein hydrolysate improves learning and memory function, alleviates neuronal damage, and reduces the deposition of pathological AD markers in AD mice, which may be related to the inhibition of neuronal ferroptosis.